Czynniki kształtujące wartość zapotrzebowania na nieodnawialną energię pierwotną EP dla budynków o niskim zużyciu energii = Factors affecting the demand value for non-renewable primary energy EP in low energy buildings - Pawłowski, Krzysztof; Nakielska, Magdalena; Buchaniec, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In order to achieve the standard of a low energy building it is needed to define the energy characteristics of the building with t-aiming at the minimal value of primary energy demand factor EP. The analysis of a building for energy saving concerns thermal parameters of external heat partitions, central heating installation efficiency, ventilation and hot water installation as well as using renewable energy sources. In this work there is an analysis of selected factors affecting PE factor in existing and new-designed buildings and there are valuable practical conclusions formulated.
Keywords: energia nieodnawialna; energia pierwotna; zużycie energii; budynek niskoenergetyczny; non-renewable energy; primary energy; energy consumption; low energy building